2010
DOI: 10.1142/s1005386710000830
|View full text |Cite
|
Sign up to set email alerts
|

Different Prime R-Ideals

Abstract: It is well known that there are several non-equivalent types of prime near-rings which are all equivalent in the case of associative rings. In this paper we introduce various characterizations of prime modules in a zero-symmetric near-ring R. The connection of a prime R-ideal P of a module M and the ideal (P:M) of the near-ring R is also investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…• P is c-prime. Proposition 2 ( Juglal et al 2010, Taşdemir et al 2011 If Pv N Γ is c-prime(equiprime), then (P:Γ)vN is c-prime(equiprime). Proposition 3 (Taşdemir et al 2011) If N is RP, Γ is monogenic and (P:Γ)vN is equiprime, then Pv N Γis equiprime.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…• P is c-prime. Proposition 2 ( Juglal et al 2010, Taşdemir et al 2011 If Pv N Γ is c-prime(equiprime), then (P:Γ)vN is c-prime(equiprime). Proposition 3 (Taşdemir et al 2011) If N is RP, Γ is monogenic and (P:Γ)vN is equiprime, then Pv N Γis equiprime.…”
Section: Introductionmentioning
confidence: 98%
“…Veldsman (1992) has examined equiprimeness in depth. Juglal et al (2010) generalized the various notions of primeness (0-, 1-, 2-, 3-, c-primeness) that were defined in a near-ring to the near-ring module. Tasdemir et al (2011) added to these five types by introducing equiprime N-ideals. N is said to be a right permutable (RP) near-ring if abc = acb for all a,b,c ∈N (Birkenmeier and Heatherly 1989).…”
Section: Introductionmentioning
confidence: 99%
“…Bhavanari et.al [6] proved the correspondence between the prime left ideals of N and that of M n (N) . Juglal et.al [7] studied different prime N-ideals and prime relations between generalized matrix nearring and multiplication modules over a nearring. Further, Juglal and Groenewald [8] studied the class of strongly prime nearring modules and shown that it forms a -special class.…”
Section: Introductionmentioning
confidence: 99%
“…Recall that modules over near rings are a generalization of near rings. In 2010, Groenewald, Juglal and Lee [7] extended prime ideals of near rings to prime Rideals of modules over near rings.…”
Section: Of Modules Over Near Ringsmentioning
confidence: 99%